2000
DOI: 10.1110/ps.9.10.1968
|View full text |Cite
|
Sign up to set email alerts
|

New insight on β‐lactoglobulin binding sites by 1‐anilinonaphthalene‐8‐sulfonate fluorescence decay

Abstract: The fluorescence time decay parameters of the b-lactoglobulin-1-anilinonaphthalene-8-sulfonate complex have been investigated under physical and chemical perturbations~2 Ͻ pH Ͻ 8 and added electrolyte 0 Ͻ NaCl Ͻ 0.5 M! to obtain new insight on the nature of the protein binding interactions. A double exponential decay of the bound probe lifetime has been confirmed by the presence of a longer component, 11 to 14.5 ns, and a shorter component, 2.5 to 3.5 ns. The two lifetimes are ascribed to different binding mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
108
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(118 citation statements)
references
References 33 publications
10
108
0
Order By: Relevance
“…ANS have been distinguished [1][2][3]. Studies of the binding energetics and crystal structure of ANS-protein complexes show that for some proteins, ANS binding depends primarily on ion pairing with positively charged side chains [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…ANS have been distinguished [1][2][3]. Studies of the binding energetics and crystal structure of ANS-protein complexes show that for some proteins, ANS binding depends primarily on ion pairing with positively charged side chains [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a small enhancement of ANS fluorescence intensity upon binding does not necessarily reflect a low binding affinity to proteins [3][4][5].…”
Section: Resolution Of Ans Binding To Tl By Time-resolved Fluorescencementioning
confidence: 94%
“…In fact, studies of lipocalin binding sites and interpretation of function are usually predicated on the assumption that the fold or cavity is the only ligand binding site in the molecule. However, external binding sites with unique characteristics were discovered for two lipocalins, α1-acid glycoprotein and β-lactoglobulin [2][3][4][5]. The careful delineation of all binding sites in lipocalins is relevant because a new classification scheme is based on comparative binding affinity analysis using retinol, retinoic acid, as well as the generic molecular probes, 11-(5-(dimethylamino)-1-naphthalene-sulfonylamino)undecanoic acid (DAUDA) and 8-anilino-1-naphtalenesulfonic acid (ANS) [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-Lg has a protein fold composed of two antiparallel β-sheets and shows a remarkable similarity to plasma retinol-binding protein ; it is a member of the lipocalin super family of transporters of hydrophobic molecules. Its physiological role is still unclear and, it has been demonstrated that β-Lg binds a variety of hydrophobic molecules such as retinol, fatty acids, triglycerides, protoporphyrin IX and ANS Fugate and Song, 1980;Collini et al, 2000;D'Alfonso et al, 1999;Andrade and Costa, 2002) β-Lg film properties such as transparency, water vapor permeability, oxygen permeability, and mechanical properties are identical to the properties of whey protein isolate films (Mate and Krochta, 1996;Anker et al, 1998). Heat denaturation opens the β-Lg globular structure, exposes sulfhydryl and hydrophobic groups, induces oxidation of free sulfhydryls, and promotes disulfide bond interchange and hydrophobic bonding thereby forming water-insoluble edible films Mate and Krochta, 1996).…”
Section: Edible Filmsmentioning
confidence: 99%